Exposure to the insecticide endosulfan induces liver morphology alterations and oxidative stress in fruit‐eating bats (Artibeus lituratus). Issue 1 (27th April 2017) - Oliveira, Jerusa Maria; Brinati, Alessandro; Miranda, Liany Divina Lima; Morais, Danielle Barbosa; Zanuncio, José Cola; Gonçalves, Reggiani Vilela; Peluzio, Maria do Carmo Gouveia; Freitas, Mariella Bontempo
Summary: Exposure to pesticides may increase the generation of reactive oxygen species (ROS), leading to oxidation of cell membrane lipids and proteins. Although fruit bats are potentially exposed to pesticides during their entire lifespan, the impacts of this exposure are still poorly investigated. We examined the effects of low, commercially recommended concentrations (0, 1.05 and 2.1 g/l) of an organochlorine insecticide endosulfan (EDS) formulation on oxidative responses in the liver and kidneys of Neotropical fruit bats ( Artibeus lituratus ), as well as possible liver morphological alterations following a 35‐day oral exposure. Superoxide dismutase activity was significantly decreased upon exposure to 1.05 g/l of EDS in the liver and kidneys, catalase was decreased in the liver of 2.1 g/l EDS‐exposed bats, while glutathione S‐transferase was increased in the liver of 2.1 g/l EDS‐exposed bats. Protein carbonyls increased following the exposure to the highest EDS dose tested. Endosulfan‐induced morphological alterations in the liver included cell degeneration and cell death, with apparent cytoplasm lipid accumulation (steatosis) and pyknotic nuclei, karyolysis and deposit of collagen fibres. Our findings suggest that exposure to low concentrations of EDS induced a certain extent of oxidative damage in fruit bats, which may have led to liver morphological alterations.